Media Framing of Donald Trump's 2024 Election Victory: A Case Study on International Media - Setiawan, Dani; Ananda, Darra; Kartika, Tina (P3M Politeknik Negeri Media Kreatif, 2025)
This article analyzes the framing differences in the coverage of Donald Trump's victory in the 2024 U.S. Presidential Election by two international media outlets, Xinhua News and The Washington Post. Using Robert N. Entman's framing analysis approach, the study explores how the two media define the problem, diagnose the cause, make moral judgments, and offer treatment recommendations regarding the political and social divisions in the United States. Xinhua News tends to emphasize optimism and solutions for the country's healing, stressing the importance of overcoming social and economic tensions. In contrast, The Washington Post is more critical, highlighting the growing political distrust and the potential impacts of Trump's policies on human rights, immigration, and the economy. These framing differences reflect the influence of media in shaping public perceptions of leadership and political policies, demonstrating how the ideological stance of media outlets can affect their portrayal of a significant political event. This research provides insights into the dynamics of media and politics in the context of elections.